Case Study Experiences on Active Learning Methods in Germany - Tudevdagva Uranchimeg; Heller Ariane; Hardt Wolfram (De Gruyter, 2021)
This article describes the implementation of active learning methods in engineering courses. The implementation was part of the activities of the international Erasmus project DriveMATH, which ran between 2017 and 2020. The active learning methods eduScrum, JigSaw, problem based learning, practical and team-based learning were used for courses for the master's degree at Chemnitz University of Technology. Research seminar computer science, research internship and internship automotive software engineering were selected as courses for implementation. The students were invited to participate in the implementation on a voluntary basis. At the end of the implementation, the project team asked the students for feedback in the form of an evaluation survey. Criteria for the evaluation were developed in the team of the partner universities of the project. The data obtained were evaluated with the help of the structure-oriented evaluation model (SURE model).